Learning climate as the strongest predictor of school performance: A multivariate analysis of the effects of instructional leadership and literacy culture - Arifin, Arifin; Jampel, I Nyoman; Sanjaya, Dewa Bagus; Widiana, I Wayan (Edelweiss Applied Science and Technology, 2026)
School performance is a critical outcome in educational management, yet the simultaneous effects of school contextual factors remain insufficiently understood, particularly in Eastern Indonesia. This study examines the effects of instructional leadership, literacy culture, and learning climate on school performance and identifies the strongest predictor. A quantitative survey was conducted with 305 public senior high school teachers in Kupang City, East Nusa Tenggara. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 5,000 bootstrap subsamples. The results showed that learning climate was the strongest predictor of school performance (β = 0.550), followed by literacy culture (β = 0.242) and instructional leadership (β = 0.226). Literacy culture was also the strongest predictor of learning climate (β = 0.686). Mediation analysis revealed that literacy culture and learning climate partially mediated the relationship between instructional leadership and school performance. The model explained 70.9% of the variance in school performance (R² = 0.709). These findings demonstrate that school performance emerges from the interplay of leadership, literacy culture, and learning climate. Practically, strengthening learning climate and literacy culture should be prioritized alongside instructional leadership to improve school performance.